Pengaruh Promosi, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian Melalui Kepercayaan Pelanggan Sebagai Variabel Intervening Pada Pelanggan Indihome di Kota Malang - Murini, Ira; Rachma, N.; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted to determine the effect of promotion, price and service quality on purchasing decisions with consumer trust as an intervening variable for Indihome customers in Malang City (empirical study at the Blimbing housing complex, Malang City). The method used is explanatory research which aims to explain the position of each variables and their influence between one variable and another variable, and the data source used is primary data by distributing Linkert scale questionnaires to Indihome customers in Malang City. The sample calculation in this study used the Malhotra formula which produced 100 respondents. The results of this research are that the promotion, price and service quality variables have a direct influence on consumer trust, the promotion, price and service quality variables have a direct influence on purchasing decisions, the consumer trust variable directly influences purchasing decisions, and the promotion, price and service quality variables have no influence. directly on purchasing decisions with consumer trust as the main factor, the intervening variable. Keywords: Promotion, Price, Service Quality, Purchasing Decisions and Customer Trust